2014
DOI: 10.1016/j.astropartphys.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A pair production telescope for medium-energy gamma-ray polarimetry

Abstract: We describe the science motivation and development of a pair production telescope for medium-energy (~5-200 MeV) gamma-ray polarimetry. Our instrument concept, the Advanced Energetic Pair Telescope (AdEPT), takes advantage of the Three-Dimensional Track Imager, a low-density gaseous time projection chamber, to achieve angular resolution within a factor of two of the pair production kinematics limit (~0.6° at 70 MeV), continuum sensitivity comparable with the Fermi-LAT front detector (<3 × 10-6 MeV cm-2 s-1 at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 85 publications
(102 reference statements)
0
66
0
Order By: Relevance
“…For medium-energy gamma-rays, other physical effects, including the nuclear recoil, limit the ultimate angular resolution of any nuclear pair-production telescope. The angular resolution is unlikely to improve by more than a factor of a few in future instruments (Bernard et al 2014;Wu et al 2014;Hunter et al 2014). Jets can be well resolved in the radio band down to sub parsec scales.…”
Section: History and Challengesmentioning
confidence: 99%
“…For medium-energy gamma-rays, other physical effects, including the nuclear recoil, limit the ultimate angular resolution of any nuclear pair-production telescope. The angular resolution is unlikely to improve by more than a factor of a few in future instruments (Bernard et al 2014;Wu et al 2014;Hunter et al 2014). Jets can be well resolved in the radio band down to sub parsec scales.…”
Section: History and Challengesmentioning
confidence: 99%
“…For the high energy emission, Zhang & Böttcher (2013) have shown that by combining the infrared/optical and the X-ray/γ-ray polarization signatures, it would be possible to distinguish the two models. Several X-ray and γ-ray polarimeters are currently proposed and/or under development (e.g., Hunter et al 2014). However, despite remarkable progress that has been made to improve these high-energy polarimeters, they commonly suffer from limited sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…These searches have been quite successful, suggesting that the LAT's utility as a seed for radio searches is given by the same performance parameters as the source detection sensitivity. 4. Pulsar Timing and Modeling.…”
Section: Galactic Sourcesmentioning
confidence: 99%